Penerapan Internet of Thing (IoT) Dalam Pengendalian Suhu, Kelembaban dan PH Air Kolam pada Mini EduFarm - Efri Suhartono; Jaspar Hasudungan; Jangkung Raharjo; Ardio Pratama Putra; Firman Ag. Roni; Annisa Puji Lestari; Ahmad Zaky Rafif Muthafa; Dega Pradipta Ramadhan; Muh Zidni Makarim; Eka Sugiarto (Journal of Information System Research (JOSH), 2023)
In cultivating fish using ponds, there are quite a number of parameters that must be considered in order to get the desired results and minimize failure in the cultivation of the fish itself. The problems that occur in fish farming according to the references obtained are the temperature and pH of the water that are not in accordance with the needs of the fish itself. Optimal water temperature conditions for intensive catfish maintenance are 25 – 30°C. Meanwhile, from time to time the temperature of the water can change due to certain factors. Based on the above problems, IoT technology is used which can identify and detect the data above, so that it can analyze the required data and automatic feeding with consistent time. Testing will be carried out by adjusting the data taken by the sensor used as well as the output from the tool itself by utilizing existing manual measuring instruments so that the data taken by the sensor itself is not in doubt the data taken by the sensor itself. Automatic temperature control devices and pool monitoring will be a solution to problems beyond human control. The tool will detect the pool temperature, if it feels like the pool water temperature needs to be warmed up, then the water will be channeled by a water pump to the heatsink attached to the cold side of the TEC, then the colder water will be put back into the pool, and vice versa when the pool water temperature feels cold. The monitoring system can make it easier for catfish breeders to monitor pond water conditions via mobile phones only with the web.